Syu’aib Controller: Innovative Digital Device for Supervision of Fraud of Dose (Mikyāl) and Weight (Mīzān) - Yusuf Hanafi; Wahyu Rahmawati; M Alifudin Ikhsan; Tsania Nur Diana (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2020)
One of the most significant issues in the Indonesian traditional markets is the reduction of dose (Mikyāl) and weight (Mīzān) done by sellers in traditional markets. As a solution to this corruptive reality, this paper offers an application called Syu'aib Controller (SC). This is a dose and weight frauds detector. With this application, consumers can control the process of selling and buying as it told in the story of the Madyans. Syu'aib Controller (SC) was developed on a digital basis based on the criteria of the Quranic values taught by the Prophet Syu'aib AS to the Madyans. These values include justice, accuracy, and satisfaction. This innovative device can be used in buying and selling activities in traditional markets. With this digital device, the buyers could know the real weight of the object, check and supervise the dose, and scale used in the traditional market. The Syu'aib Controller (SC) is expected to foster an anti-corruption mentality. Thus the fair and honest characters of the Nusantara merchants are formed.